2019
DOI: 10.3389/fenrg.2019.00101
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Azo Dye (Acid Orange 7) in a Microbial Fuel Cell: Comparison Between Anodic Microbial-Mediated Reduction and Cathodic Laccase-Mediated Oxidation

Abstract: More than 80% of wastewater from industries is discharged into receiving water bodies without any pollution control. Microbial fuel cells (MFCs) are a promising technology for the simultaneous treatment of wastewater and electricity production. With regard to azo-dye containing wastewater (e.g., from textile manufacturing), the dye may be fed via the anode chamber containing electrochemically active bacteria or via the cathode chamber containing laccase enzyme as catalyst for oxygen reduction. This study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…The initial rapid decolourization is due to the high enzyme activity initially; the rate of decolourization decreases gradually as the enzyme activity decreases as shown in the enzyme activity graphs ( Figure 7 ). The dye decolourization by laccase is probably due to asymmetric cleavage of the azo-bonds and subsequent ring cleavage to form simple aromatic compounds (Mani et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial rapid decolourization is due to the high enzyme activity initially; the rate of decolourization decreases gradually as the enzyme activity decreases as shown in the enzyme activity graphs ( Figure 7 ). The dye decolourization by laccase is probably due to asymmetric cleavage of the azo-bonds and subsequent ring cleavage to form simple aromatic compounds (Mani et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Laccase is a multi-copper containing oxidase enzyme which is capable of one electron oxidation of other substrates and four electron reduction of O 2 to H 2 O (Galhaup and Haltrich, 2001 ). Laccase has been employed in the cathode chamber of MFC for dye decolourization and catalysis of the oxygen reduction reaction (Savizi et al, 2012 ; Mani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The azo dyes degradation with laccases begins with the asymmetric excision of the azo bond followed by oxidative excision, desulfonation, deamination, demethylation or dihydroxylation, depending on the structure of the dye [160]. Discolouration of azo class dyes such as Methyl Orange (MO) has reported using Aspergillus ochraceus laccase NCIM-1146 [289], Congo Red (CO), with Tplac laccase from Trametes pubescens [280], Acid Orange 7 (AO7) using a laccase (not specified), [290]. In the three works, it was identified that in azo dyes, the first step in the discolouration is the splitting of the bond -N=N-, which results in obtaining two asymmetric intermediate products (Figure 4), [289][290][291].…”
Section: Degradation Of Synthetic Dyes By Laccasesmentioning
confidence: 99%
“…Discolouration of azo class dyes such as Methyl Orange (MO) has reported using Aspergillus ochraceus laccase NCIM-1146 [289], Congo Red (CO), with Tplac laccase from Trametes pubescens [280], Acid Orange 7 (AO7) using a laccase (not specified), [290]. In the three works, it was identified that in azo dyes, the first step in the discolouration is the splitting of the bond -N=N-, which results in obtaining two asymmetric intermediate products (Figure 4), [289][290][291]. The mechanism that the laccases carry out for the excision of azo dyes is through the formation of an electron-deficient reaction centre (carbocation).…”
Section: Degradation Of Synthetic Dyes By Laccasesmentioning
confidence: 99%
“…Therefore, eco-friendly technology is crucially needed to transform organic pollutants present in the water into less toxic molecules or to completely degrade them into CO 2 and H 2 O [5]. Traditional approaches, such as coagulation, adsorption, chemical oxidation, chemical reduction [6], photocatalytic oxidation [7], and enzymatic degradation [8], are widely exploited to eliminate organic pollutants from effluents. However, they display some limitations [9], such as the need for complementary treatments before their elimination at wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%